Efficient information hiding in medical optical images based on piecewise linear chaotic maps - Nasr, Marwa A.; El-Shafai, Walid; Abdel-Salam, Nariman; El-Rabaie, El-Sayed M.; El-Fishawy, Adel S.; El-Samie, Fathi E. Abd (Journal of optics (New Delhi), 2023)
Steganography is one of the fascinating subjects for researchers. One of the recent research trends in this field is audio steganography, which depends on hiding of information in the cover file, while only the sender and the recipient know that there is a secret content. This technique achieves more information security and protects the image from unauthorized access. Based on the Short-Time Fourier Transform (STFT), this paper provides a new audio steganography technique for concealing medical images in audio files. The medical image is encrypted using a Piece-Wise Linear Chaotic Map (PWLCM)-based bit-level image encryption technique. In addition, the image is processed as a spectrogram and converted into a speech-like signal through the STFT before embedding it within the cover audio file. The proposed technique is carried out on four different medical images, and four audio files of suitable size. Furthermore, it is validated by comparing it with the works in the literature. The comparison reveals that the proposed audio steganography technique reveals a superior performance regarding the quality of encryption and confidentiality of medical images, as the pre-stage with the PWLCM provides more security, and good restoration quality as it achieves a Peak Signal-to-Noise Ratio (PSNR) of 55.25 dB, and a Mean Square Error (MSE) of 2.9×10 -6 .